ECONOMIC ASPECTS OF MANAGING INCOME AND CONSUMER SPENDING IN AN INFLATIONARY ENVIRONMENT (Spectrum Journal of Innovation, Reforms and Development, 2026)
This article examines the economic aspects of managing household income and consumer spending under inflationary conditions. Inflation reduces the purchasing power of money, changes consumption priorities, increases uncertainty and forces households to reconsider saving, borrowing and expenditure decisions. The article analyzes real and nominal income, consumer behavior, inflation expectations, essential and discretionary spending, household budgeting, debt management, savings protection and the role of state economic policy. It is argued that effective income and expenditure management in an inflationary environment requires a combination of financial literacy, rational consumption, wage adjustment, social protection and macroeconomic stabilization.